Detection of Florfenicol and Toltrazuril residues in broiler liver samples collected from Latakia markets – Syria (Latakia University Journal -Biological Sciences Series, 2021)
The study aimed to detect the content of broiler liver from Florfenicol and Toltrazuril residues, and compare results with the maximum residue limits (MRLs) allowed locally and internationally, to assess the safety of its human consumption. 96 random samples of broiler liver were collected from markets of Latakia during 2018, and they were extracted and analyzed using high-performance liquid chromatography instrument in laboratories of the Ministry of Agriculture in Damascus.The results showed an increase in the levels of Florfenicol and Toltrazuril in samples, as they ranged between (249.71 -3842.58) and (22.16 -884.35) µg/ kg, respectively, 75 and 100% of the samples contained residues of these two compounds, 16.7 and 20% of the total samples exceeded the MRL in broiler livers. This necessitates the necessity of strict monitoring of the antibiotic content in chicken meat before it is put up for human consumption.Statistical analysis indicates significant differences P≤0.05 when comparing mean of Florfenicol and Toltrazuril in samples of the third quarter with the mean of other quarters. While no differences were recorded when comparing the mean of the remaining quarters with each other.